This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
2 n − 2 n − 1 2 n − 1 ( 2 − 1 ) 2 n − 1 lo g 2 ( 2 n − 1 ) n − 1 = 2 x = 2 x = 2 x = lo g 2 ( 2 x ) = x
We first write out the original equation.
2 n − 2 n − 1 = 2 ?
Then, we write 2 n as 2 ∗ 2 n − 1
( 2 − 1 ) ∗ 2 n − 1 = 2 ?
2 n = 2 ?
FInally, we see that the ? is equal to n-1, so n − 1 is the answer.
@Shining Sun , you don't need to split the formula with many \ ( \ ) . LaTex code is much easier and looks much better that way. I have edited your solution. Braces { } is unnecessary if there is only one character.
Problem Loading...
Note Loading...
Set Loading...
2 n − 2 n − 1 2 n − 1 ( 2 − 1 ) 2 n − 1 ⟹ x = 2 x = 2 x = 2 x = n − 1